Berberine$1 (Bs Therapeutic Prospects in Parkinson$1 (Bs Disease: A Spotlight on Cholesterol Regulation for Cognitive Improvements - T Lakshmi Narayanan
Cholesterol synthesized in astrocytes of the cerebrum plays a pivotal role in regulating hippocampal neurogenesis and cognitive function. Dysregulation of cholesterol metabolism has emerged as a key contributor to the pathogenesis of Parkinson$1 (Bs disease. Elevated cholesterol levels in the brain are associated with increased oxidative stress and subsequent neurodegeneration of hippocampal pyramidal neurons, culminating in cognitive impairment. Berberine, an isoquinoline alkaloid has the potential to modulate cholesterol synthesis through HMG-CoA inhibition.s